Nurses and Midwives Mistakes and Errors in Pediatric Health Outcomes in Southwestern Uganda - Milly Akantorana; Raymond Tumwesigye; Concepta Mary Nalwanga; Vallence Niyonzima; Rachel Luwaga; Esther Beebwa (Pediatric Health, Medicine and Therapeutics, 2026)
Background: According to the World Health Organization, nearly 1 in 10 patients suffer harm during healthcare, resulting in over 3 million deaths in low- and middle-income countries. Alarmingly, more than half of these incidents are preventable, with medication errors being the primary cause. Children are particularly vulnerable to these errors and other adverse patient events. Therefore, this study explored nurses and midwives’ mistakes and errors in paediatric health outcomes in southwestern Uganda. Methods: We adopted a phenomenological qualitative research design. Purposive and consecutive sampling methods were used to recruit nurses and midwives who had served in their respective units for at least six months and were willing to participate and signed a written informed consent form. Data collection was done using a semi-structured interview guide. All interviews were face-to-face and audio-recorded upon participants’ consent. Thematic analysis was used to generate the themes. Results: The study revealed four themes that emerged from participants’ perceptions regarding the reasons for pediatric medication errors namely; work flow and work environment, work overload, limited resources and training and education need. Regarding participants’ experience of pediatric medication errors, omission and commission errors was quoted and three themes emerged from interventions to medication errors, namely; sticking to rights of drug administration, education and training, and resources. Conclusion: Results of this study indicate that although nurses demonstrated positive perceptions of strategies to improve pediatric medication safety, medication errors remain a serious challenge requiring close supervision. The primary problem identified as quoted verbatim by the participants is “…overcrowding of babies in limited clinical spaces”, which created a high-risk environment for errors. The findings highlight the urgent need to incorporate the voices of nurses into policy, education, and training initiatives. Such inclusion will contribute to the development of robust healthcare systems and more effective strategies to enhance pediatric medication safety
Keywords: Medication errors; Pediatrics; Experiences; Perceptions